2012
DOI: 10.3171/2012.7.gks121019
|View full text |Cite
|
Sign up to set email alerts
|

Same-day stereotactic aspiration and Gamma Knife surgery for cystic intracranial tumors

Abstract: Object The goal of this study was to evaluate the efficacy and safety of same-day stereotactic aspiration and Gamma knife surgery (GKS) for cystic intracranial tumors. Methods Between 1996 and 2007, 77 patients harboring cystic intracranial tumors underwent a same-day procedure of MRI-guided cyst aspiration followed by GKS. The diagnoses were metastatic tumor in 43 patients, glial tumor in 12 patients, vestibular schwannoma in 10 patients, craniopharyngioma in 9 patients, and hemangioblastoma in 3 patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 20 publications
(20 reference statements)
2
18
0
Order By: Relevance
“…After the procedure, a single cyst provides an effective target for cyst volume reduction using stereotactic radiotherapy. Stereotactic cyst aspiration and gamma knife radiosurgery may be achieved on the same day using one stereotactic frame application for cystic glial tumors or craniopharyngiomas, as reported recently (22). The authors of the study performed repeated aspiration via Ommaya reservoir with 14 of 77 patients (18.2%).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 95%
“…After the procedure, a single cyst provides an effective target for cyst volume reduction using stereotactic radiotherapy. Stereotactic cyst aspiration and gamma knife radiosurgery may be achieved on the same day using one stereotactic frame application for cystic glial tumors or craniopharyngiomas, as reported recently (22). The authors of the study performed repeated aspiration via Ommaya reservoir with 14 of 77 patients (18.2%).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 95%
“…3). 14,26,33 Debates Although the beneficial effect of radiation in the treatment of craniopharyngiomas has been well recognized, 2 critical issues remain sources of significant controversy: 1) the merits of GTR versus subtotal resection followed by irradiation given the surgical morbidity and mortality rates associated with aggressive resection and 2) the role of RT immediately after resection without first monitoring for tumor progression and the role of RT in the absence of resection (up-front or salvage treatment).…”
Section: Cyst Development and Enlargement During Radiation Therapymentioning
confidence: 99%
“…Liu et al exploited needle aspiration to 77 patients with cystic intracranial tumors, followed by Gamma Knife surgery. 85 88.3% of patients showed improved symptoms immediately after cyst aspiration. The authors found that such a reduction of the volume of tumors improved the effectiveness of the Gamma Knife by enabling a higher radiation dose, while lowering the risk of complications.…”
Section: Stereotactic Needle-based Aspirationmentioning
confidence: 91%